Amethyst leaf extract as pest control and fertilizer for soybean plants (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rumape O, Kilo A, Ischak NI. 2022. Amethyst leaf extract as pest control and fertilizer for soybean plants. Biodiversitas 23: 3355-3363. Amethyst (Datura metel L.) is a plant that grows and develops in the Gorontalo area, and people use it as traditional medicine. This plant has a natural insecticidal activity that is not yet known by the general public. So far, the results of research on natural insecticides from amethyst have only been tested on a small scale in the laboratory, not yet applied on a large scale in the garden. The purpose of this study was to extract amethyst leaves and apply it as an inhibitor of feeding activity and insect mortality in both the laboratory and soybean gardens. Amethyst leaves were extracted in the laboratory using methanol, n-hexane, and ethyl acetate. The extracts were tested phytochemically to determine the type of secondary metabolite, before applying it. Phytochemical test showed amethyst leaves contain alkaloid, flavonoid, terpenoid, and saponin. The application treatment for the bioactivity used variations in the concentration of amethyst leaf extract of the fractions (methanol, ethyl acetate and n-hexane), namely 1.0, 2.5, 5.0, 7.5, 10%; and 0% as control. In the laboratory, the treatment was applied by contact to 5 insects Spodoptera litura instar III for each concentration treatment with 3 replications. Observation parameters were the percentage decrease in feeding activity and mortality of Spodoptera litura larvae. In the garden, the extracts with varying concentrations of the same as in the laboratory, were applied to soybeans treated with the pest Spodoptera liturain a closed container, and the other was sprayed on plants that were left exposed. The results showed that the three extracts could kill pests, but n-hexane extract was the most effective compared to ethyl acetate and methanol extracts. Amazingly, soybean plants whose yellow leaves turn green after being given the extract. This indicates that the secondary metabolites of amethyst are not only used as insecticides to control pests, but also as plant fertilizers.